A decade of review in global regulation and research of artificial intelligence medical devices (2015–2025) - Zhang, Siwen; Li, Yujun; Liu, Wenxi; Chu, Qi; Wang, Shasha; Li, Jinyu; Chen, Yuwen (Frontiers in Medicine, 2025)
Artificial intelligence (AI) and medical devices are increasingly integrated, reshaping global diagnostic paradigms. However, the adaptive learning and opaque nature of AI technologies pose significant challenges to traditional regulatory frameworks. In response, regulatory bodies worldwide, including the U.S., EU, China, Japan, and South Korea, have initiated various policies to address the unique risks posed by AI medical devices (AIMD). These efforts aim to balance innovation with patient safety, yet gaps remain in harmonizing standards across regions and ensuring comprehensive oversight. This study provides a comprehensive analysis of the regulatory policies for AIMD from 2015 to 2025 across key global regions. We examine the evolution of these policies, the academic research progress, the limitations of existing regulations, and emerging trends. By reviewing relevant legislation and literature, this paper offers valuable insights for researchers, manufacturers, and regulators to foster the development of robust regulatory frameworks for AIMD.